2018
DOI: 10.1016/j.bmcl.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and in vitro evaluation of quinolinyl analogues for α-synuclein aggregation

Abstract: Here we report the synthesis and in vitro evaluation of 25 new quinolinyl analogues for α-synuclein aggregates. Three lead compounds were subsequently labeled with carbon-11 or fluorine-18 to directly assess their potency in a direct radioactive competitive binding assay ng both α-synuclein fibrils and tissue homogenates from Alzheimer's disease (AD) cases. The modest binding affinities of these three radioligands toward α-synuclein were comparable with results from the Thioflavin T fluorescence assay. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…After tritiation, [ 3 H]MODAG-001 was tested in saturation binding experiments against human recombinant fibrils and showed very high affinity to αSYN fibrils, with a K d value of 0.6 nM in vitro. Compared to [ 3 H]MODAG-001, all the compounds, which have been described in the literature as potential αSYN PET ligands, showed an at least one order of magnitude lower binding affinity (higher K d values) in vitro towards recombinant αSYN fibrils [ 14 , 21 , 24 31 ]. These compounds comprise [ 125 I]SIL23, ( K d = 148 nM) and its derivative SIL26 ( K i = 15.5 nM), [ 24 ] [ 18 F]BF-227 ( K d = 9.6 nM) [ 26 ], several fluorescent probes ( K d s in the micromolar and elevated nanomolar range) [ 32 , 33 ], and the 18 F-labeled 3-(benzylidine)indolin-2-one derivative [ 18 F]46a ( K d = 8.9 nM) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After tritiation, [ 3 H]MODAG-001 was tested in saturation binding experiments against human recombinant fibrils and showed very high affinity to αSYN fibrils, with a K d value of 0.6 nM in vitro. Compared to [ 3 H]MODAG-001, all the compounds, which have been described in the literature as potential αSYN PET ligands, showed an at least one order of magnitude lower binding affinity (higher K d values) in vitro towards recombinant αSYN fibrils [ 14 , 21 , 24 31 ]. These compounds comprise [ 125 I]SIL23, ( K d = 148 nM) and its derivative SIL26 ( K i = 15.5 nM), [ 24 ] [ 18 F]BF-227 ( K d = 9.6 nM) [ 26 ], several fluorescent probes ( K d s in the micromolar and elevated nanomolar range) [ 32 , 33 ], and the 18 F-labeled 3-(benzylidine)indolin-2-one derivative [ 18 F]46a ( K d = 8.9 nM) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years, several attempts have been made to develop an αSYN-specific PET tracer [ 14 , 21 , 24 31 ]. However, the low abundance of αSYN inclusions and high similarity to structurally related proteins present in pathological brain regions [ 51 , 55 ] made its discovery very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds containing a quinolinyl moiety and six-membered aromatic rings linked either by a double bond or an oxadiazole bridge were designed by Yue et al for α-syn imaging [ 134 ]. A rational design approach was applied based on previous findings combining key features of the compounds LDS 798 and 2,6-ANS ( Figure 5 ).…”
Section: Alpha-synuclein Pet Tracer Development—from a Molecular Development Point Of Viewmentioning
confidence: 99%
“…Using recombinant α-syn fibrils and brain AD tissue homogenates, the affinity of these compounds was determined to be 21, 79, 18 nM for [ 11 C]52 , [ 18 F]53 , [ 18 F]54 , respectively. Affinity toward Aβ fibrils was determined to be in the same order of magnitude [ 134 ]. These binding characteristics discouraged the authors from further evaluating the compounds in vivo.…”
Section: Alpha-synuclein Pet Tracer Development—from a Molecular Development Point Of Viewmentioning
confidence: 99%
“…Comprehensive and vivid literature is available that highlight the therapeutic value of this pyridine derivative [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Notably, Gilani et al showed that isonicotinic acid-derived 1,3,4-oxadiazoles exhibited an interesting profile of anti-inflammatory activity, which was superior to the standard drug Naproxen [ 19 ].…”
Section: Introductionmentioning
confidence: 99%